2016
DOI: 10.7324/jabb.2016.40308
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and identification of Salmonella spp. from broiler and their antibiogram study in Sylhet, Bangladesh

Abstract: The objectives of this study were to isolate the associated Salmonella spp. from cloacal swabs of broiler and their antibiogram studies. A total of 80 cloacal swabs comprising of 50 samples of apparently healthy broiler and 30 samples of diarrheic broiler were collected from different poultry farms at Sylhet, Bangladesh during Ja nuary to June 2013. The samples were subjected for isolation and identification of Salmonella spp. through a series of conventional bacteriological studies like study of morphology, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 13 publications
2
3
1
Order By: Relevance
“…However, Egyptian studies of Sedeik et al (2019) and El-Sheikh et al (2019) showed isolation of Salmonellae from broiler chicks in rates of 7.5% and 16%, respectively. Regarding the colonial morphology and biochemical tests results of Salmonella, parallel results were also described by Akeila et al (2013), Islam et al (2016), Al-Mamun et al (2017 and Mridha et al (2020). Moreover, the serological results of the isolated Salmonellae showed that S. enteritidis and S. kentucky were the most among the isolates.…”
Section: Discussionsupporting
confidence: 75%
“…However, Egyptian studies of Sedeik et al (2019) and El-Sheikh et al (2019) showed isolation of Salmonellae from broiler chicks in rates of 7.5% and 16%, respectively. Regarding the colonial morphology and biochemical tests results of Salmonella, parallel results were also described by Akeila et al (2013), Islam et al (2016), Al-Mamun et al (2017 and Mridha et al (2020). Moreover, the serological results of the isolated Salmonellae showed that S. enteritidis and S. kentucky were the most among the isolates.…”
Section: Discussionsupporting
confidence: 75%
“…The studies conducted in Bangladesh, S . Typhimurium was found to be 15.91% in broiler production systems [ 80 ]; 85% in broiler farm samples [ 31 ] and 5% in commercial layer farm settings [ 81 ]. S .…”
Section: Discussionmentioning
confidence: 99%
“…Many cultures of Salmonella spp. may also produce large colonies with glossy black centers or may appear as almost completely black (Sujatha et al 2003;Ramya et al 2012;Rabie et al 2012;Islam et al 2016). Our results revealed that a suspected 49 Salmonella isolates out of 500 collected samples were detected by morphological and biochemical examination (Table 1).…”
Section: Discussionsupporting
confidence: 48%